Autoethnography In Photography Research Of The Self - Kurniawan, Donie Fadjar; Lukistyawan, Purwastya Pratmajaya Adi; Sudarwanto, Aan; Purnomo, Agung; Tuminah, Tuminah (Journal of Urban Society's Arts, 2023)
The focus of this research is to describe a concept of auto-ethnographic research that is based on an understanding of the ethnographic view. The aim is to encourage those with a background in the arts to get detailed information about this type of auto-ethnographic research. The urgency is to strengthen auto-ethnography into artistic research (about art) from their own experiences.  The research departs from the literature review. Data was obtained through literature research by relying on primary data in the form of an article entitled An Autoethnography on Learning About Autoethnography. This article was written by Sarah Wall (2006). The work, Fitting the Methodology with the Research: An exploration of narrative, self-study and Autoethnography written by Mary Lynn Hamilton, Laura Smith & Kristen Worthington (2008) as supporting methodology. The work Artistic Research: The Thoughts And Ideas Of Mika Hannula written by Guntur (2020) to support the artistic. The case study used Self-Reflection in Mirrors in Photographic Works by Sepba Fri Atnin. (2018). The results of the study are first the concept of research on qualitative data sources that come from the researchers themselves. Second, its application in the field of arts such as recording media arts, visual arts, fine arts, dance, and performing arts.